2019
DOI: 10.1007/s11067-019-09466-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of Complex Networks Theory in Urban Traffic Network Researches

Abstract: Complex network theory is a multidisciplinary research direction of complexity science which has experienced a rapid surge of interest over the last two decades. Its applications in land-based urban traffic network studies have been fruitful, but have suffered from the lack of a systematic cognitive and integration framework. This paper reviews complex network theory related knowledge and discusses its applications in urban traffic network studies in several directions. This includes network representation met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 113 publications
(57 citation statements)
references
References 182 publications
0
57
0
Order By: Relevance
“…The rudimentary concepts and content of complex network theory have already been thoroughly introduced in some previous articles [10,94], and its related applications in urban traffic have been fully discussed [15]. From these experiences and cognitions, we can clearly see that the applications of complex network theory in land-use and transport interaction have certain phases and characteristics ( Figure 1), and they were taken from graph theory and applied to land-use by Urban and Keitt [95].…”
Section: The Complex Network Theory-based Urban Land-use and Transpormentioning
confidence: 97%
See 2 more Smart Citations
“…The rudimentary concepts and content of complex network theory have already been thoroughly introduced in some previous articles [10,94], and its related applications in urban traffic have been fully discussed [15]. From these experiences and cognitions, we can clearly see that the applications of complex network theory in land-use and transport interaction have certain phases and characteristics ( Figure 1), and they were taken from graph theory and applied to land-use by Urban and Keitt [95].…”
Section: The Complex Network Theory-based Urban Land-use and Transpormentioning
confidence: 97%
“…In these reviews, the theoretical contexts for conceptual and existing empirical research of land-use and transportation have been discussed thoroughly, and most of the land-use and transport interaction (LUTI) models have been addressed. The complex network development processes, related theory, and research on urban traffic networks have been summarized by Ding, Ujang et al [15]. Hence, this article will emphasize and further discuss complex network theory in the context of land-use and transport interaction studies and applications.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…With the obtained estimates for β , they demonstrated that the estimated interaction flows coincide reasonably well with observed interaction flows, which argues for the effectiveness of the gravity model in determining spatial interactions of freight movements. Recently, Ding et al 33 reviewed the applications of complex network theory in urban traffic studies. Our study differs from theirs in terms of the activity space (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…With the critical role of urban tra c networks in the urban economy, the characteristics and properties of urban tra c network topology have recently gained increasing attention [1][2][3][4][5][6][7][8][9][10][11][12]. Scholars have presented in-depth discussions of the process of tra c planning and design from the perspectives of network topology, tra c ow, tra c congestion, network evolution, cascade failure, and network optimization [13][14][15][16][17][18][19][20]. Nevertheless, few studies on optimal network topology consider which network structure can bear more tra c ow, how to achieve a more e cient network structure, or which network can have the greatest anticongestion ability.…”
Section: Introductionmentioning
confidence: 99%